Trigger warning short fictions and disturbances - Gaiman, Neil (New York William Morrow, 2015)
This third collection of short fiction by Gaiman includes previously published pieces of short fiction--stories, verse, and a Doctor Who story written for the series' fiftieth anniversary (Nothing o'clock). There is also "Black Dog," a new tale that revisits the world of his novel American Gods. The collection explores the masks we all wear and the people we are beneath them to reveal our vulnerabilities and our truest selves. Horror and ghosts stories, science fiction and fairy tales, fabulism and poetry explore the realm of experience and emotion. In "Adventure Story"--a thematic companion to The Ocean at the End of the Lane--Gaiman ponders death and the way people take their stories with them when they die. His social media experience "A Calendar of Tales" are short takes inspired by replies to fan tweets about the months of the year--stories of pirates and the March winds, an igloo made of books, and a Mother's Day card that portends disturbances in the universe. Gaiman offers his own spin on Sherlock Holmes in his award-nominated mystery tale "The Case of Death and Honey". And "Click-Clack the Rattlebag" explains the creaks and clatter we hear when we're all alone in the darkness.
Introduction -- Making a chair -- A lunar labyrinth -- The thing about Cassandra -- Down to a sunless sea -- "The truth is a cave in the Black Mountains ..." -- My last landlady -- Adventure story -- Orange -- A calendar of tales -- The case of death and honey -- The man who forgot Ray Bradbury -- Jerusalem -- Click-Clack the rattlebag -- An invocation of incuriosity -- "And weep, like Alexander" -- Nothing o'clock -- Diamonds and pearls: a fairy tale -- The return of the thin white duke -- Feminine endings -- Observing the formalities -- The sleeper and the spindle -- Witch work -- In Relig Odhrâain -- Black Dog.
Keywords: Holmes, Sherlock -- Fiction; Doctor -- (Fictitious character) -- Fiction; Identity (Psychology) -- Fiction; Death -- Fiction; Vulnerability (Personality trait) -- Fiction; Emotions -- Fiction; Short stories; Short stories -- Horror fiction -- Ghost stories -- Short stories